Performance of new flat fan nozzle design in spray deposition, penetration and control of soybean rust - Negrisoli, Matheus Mereb [UNESP]; Raetano, Carlos Gilberto [UNESP]; Souza, Diego Miranda de [UNESP]; Santos e Souza, Felipe Matheus; Bernardes, Laryssa Moreira [UNESP]; Del Bem Junior, Luciano [UNESP]; Rodrigues, Danilo Morilha [UNESP]; Pereira Sartori, Maria Marcia [UNESP] (Springer, 2019)
Fungicide application technology to control soybean rust (SBR) is lacking and requires optimization to improve spray coverage in the lower part of the crop canopy as well as the spray distribution uniformity. The goal of this study was to evaluate the effects of flat fan nozzles with different angles and spray volumes on the optimization of fungicide application in soybean, as well as on SBR and its effect on crop yield. For this purpose, a 2-year (2016-2018) field experiment was conducted in Botucatu, SP, Brazil. Three spray nozzles were evaluated: flat fan, double flat fan and angled flat fan, with two spray volumes. A quantitative analysis of the spray deposition was conducted, assessing the spray deposits on the lower and upper part of the plants with Brilliant Blue tracer. Furthermore, SBR severity was evaluated based on the number of pustules cm(-2) and on the AUDPC, as well as the establishment of treatment control efficacy and its effect on soybean yield. Irrespective of the spray nozzles and volumes, the penetration of the droplets into the crop canopy was impaired at the reproductive stage, with less deposition in the lower part of the plant, although the larger spray volume provided greater spray deposition. All the treatments promoted effective control of the disease, with no changes in efficacy due to a larger spray volume or angled nozzles. The correct spray volume, especially with respect to the different growth stages, greatly influences spray deposition and penetration.
Keywords: Fungicide application technology; Phakopsora pachyrhizi; Plant protection; Droplet penetration; Spray nozzle